EFFECT OF THREE INTERVENTION PROGRAMS ON FEAR OF FALLING AND FUNCTIONALITY: A RANDOMIZED CONTROLLED TRIAL. (16th November 2018) - Curcio, C; Dueñas, E; Ponce, E; Ramirez, L
Abstract: Fear of falling (FoF) and reduction in physical functioning is common among older people. The objective of this study was to evaluate the effectiveness of three intervention programs to decrease fear of falling and improve physical functioning among older people with FoF and functional limitation. A randomized controlled trial was conducted (identifier NCT03211429). A hundred and twenty-five individuals were randomized to one of three interventions: Tai Chi (TC), cognitive behavioral therapy (CBT), or a control exercise group (PC). The primary outcomes were fear of falling and functionality. All postural interventions were performed weekly for 8 weeks. Compared to baseline, fear of falls significantly reduced in all groups (effect sizes d Cohen) TC 0.37, CBT 0.80, and PC 0.71). Similarly, compared to baseline, physical functioning improved in all groups (effect sizes: TC -0.49, CBT -0.49, and PC -0.83). In summary, the three intervention programs are effective on FoF and functionality, but, CBT is most effective on FoF and CP most effective for physical functioning.